Dynamics of Self-Awareness and Transcendental Experience in High School Students: A Phenomenological Study from the Perspective of the Psychology of Religion - Fadilla Neva Ariyana; Siti Nurlaila; Sindegi Afsana Oktaviani Ramadhan; Miranda Miranda; Surawan Surawan (International Journal of Education and Literature, 2026)
This study aims to understand the dynamics of self-awareness and transcendental experiences in high school students from the perspective of the psychology of religion. Adolescence is a developmental phase characterized by the search for identity, self-reflection, and increased spiritual awareness. This study used a qualitative approach with phenomenological methods to explore students' subjective experiences related to self-awareness and spiritual experiences. The study participants consisted of two high school students aged 15–18, selected using a purposive sampling technique. Data collection was conducted through in-depth semi-structured interviews supported by field notes. The data were analyzed using phenomenological analysis through the stages of phenomenological reduction, identification of key statements, grouping themes, and essential descriptions of experiences. The results indicate that spiritual experiences in worship practices foster a sense of closeness to God, encourage self-reflection, help students cope with stress, and foster awareness to improve behavior. These findings suggest that transcendental experiences play a significant role in the development of self-awareness and character formation in adolescents.